Análise das condições ambientais do estuário do Rio Poxim e pressupostos a sua gestão - Santos, Ester Milena dos (2021)
Estuarine environments have a high population density that threatens the quality of their natural resources. Naturally, they have internal factors that favor high frequency changes, making it difficult to assess changes from external sources. In Brazil there is a slight negligence associated with management and the need for ongoing studies in these areas. This study aims to contribute to the process of integrated management of watersheds and estuarine systems and has the research hypothesis that "the understanding of environmental conditions makes it possible to carry out a critical analysis of the use and occupation in the estuary and contributes to the formulation of proposals for its management". The construction of the dissertation takes place in the format of three articles under the following specific objectives: Understand the urban advance in the areas that border the estuary, considering the pollution conditions; Diagnose the environmental conditions found in the areas outside the estuary with the perception of the local population; Assess water quality by investigating spatial and seasonal trends given the framing targets. To understand the dynamics, satellite images were analyzed over a 28-year period of the areas that border the estuary, in addition to the survey of pollution conditions through bibliographical research and estimation of the polluting potential. In order to obtain the contribution of local residents, the perception tool used was questionnaires with 28 questions on environmental themes, health and basic sanitation, transmitted online on social networks and statistical analysis of the results. And in the investigation of water quality, a sampling plan specific to estuaries and analysis of the compliance of parameters such as dissolved oxygen, salinity and total phosphorus. As a result, it was found that the greatest variations in urban growth occurred in the period between 1990 and 2000, around 23%, driven by the city's economic growth. The biggest reduction in vegetation occurred between 2010 and 2016, approximately a loss of 37%, driven by real estate pressure. Between 2016 and 2018 there was a densification of the consolidated urban space. More than 70% of neighborhood residents had water, sewage and solid waste services provided by public agencies, around 44% reported having been affected by some episode of flooding and 19% were affected by diseases such as dengue or chikungunya. Between 30% and 70% qualify the health and sanitation services offered in their neighborhoods as regular/good, but consider the performance of public authorities as bad/very bad, and more than 50% of them do not get involved in spaces intended for participation active. As for water quality, changes in dissolved oxygen and total phosphorus indicate pollution by sewage and for the dry season and points in the central estuary, the Compliance Index (CCME WQI) qualifies as poor, moving away from the desired levels for the classes of framing. It is concluded that these environments challenge managers and researchers and require continuous monitoring and a democratic, effective and integrative management process.